Sentiment Analysis of Non-Fungible Token (NFT) on Twitter Social Media Using Support Vector Machine Method - Suci Br Kembaren; Siti Saidah; Arifin Nur Rahmad; Luky Fabrianto; Novianti Madhona Faizah (Institute of Computer Science (IOCS), 2022)
Social media Twitter is used as an expression of opinion for the global community, especially in Indonesia. Non-Fungible Token (NFT) also has public opinion, sentiment from opinion can be classified into two classes, negative sentiment and positive sentiment. Using the keyword